Quantifier le genre dans les médias - Laetitia Biscarrat; Marlène Coulomb-Gully; David Doukhan; Cécile Méadel (Communication)
This paper looks at the methodological challenges facing an international study aimed at measuring the place of women in the news media. It is based on the benchmark survey in the field, the Global Media Monitoring Project (GMMP). Going beyond the survey results (available elsewhere), we examine the conditions under which the figures provided here were produced, offer a critical analysis of the results, broaden the line of questioning to an intersectional perspective by considering yet unexploited original corpora, and lastly consider the contribution of artificial intelligence by comparing manual and automated counting processes.